The Effects of Multinational Companies on Deforestation: The Building Block or Stumbling Block - DIGDOWISEISO, Kumba; SUGIYANTO, Eko (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.v11.1(41).01, 2020)
Trade liberalization and worldwide economic integration have brought not only an increase in wealth but also in transnational threats. Environmental devastation caused by commercial activities of multinational corporations (MNCs) is one of such threats. While almost all countries have environmental laws designed from pollution, the rules differ per country. Yet, only in the context of legally binding regulatory measures should multinationals be compelled to conduct business in an environmentally friendly manner.